Dhikr Therapy to Improve Gratitude - Nadya Novia Rahman; Rina Rifayanti; Yola Ratnadewani Wibowo; Malda Sabathapranatalie Chessi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study aims to determine whether there is an increase in gratitude after being given dhikr therapy training to students of the Faculty of Social and Political Sciences, Mulawarman University. This study uses a quantitative experimental method. The subjects in this study were 18 students of the Department of Psychology Faculty of Social and Political Sciences, Mulawarman University, using a purposive sampling technique. The data collection method used is a gratitude scale as a pretest and posttest. The training was carried out in 1 meeting by measuring before the training (pretest) and after the training ended (posttest). Data were analyzed by Wilcoxon rank test using SPSS 25.0 for windows. The results of the study showed that: (1) there was a significant increase in gratitude after being given dhikr therapy with statistical results (Z) = -2.677 and p = 0.007 (p less than 0.05); (2) there was no difference in gratitude scores before and after in the control group which was not given dhikr therapy with statistical results (Z) = -1.409 and p = 0.159 (p more than 0.05).Abstrak: Penelitian ini bertujuan untuk mengetahui apakah ada peningkatan rasa syukur setelah diberikan pelatihan terapi dzikir kepada mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman. Penelitian ini menggunakan metode eksperimen kuantitatif. Subjek dalam penelitian ini adalah 18 mahasiswa Jurusan Psikologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman dengan menggunakan teknik purposive sampling. Metode pengumpulan data yang digunakan adalah skala syukur sebagai pretest dan posttest. Pelatihan dilaksanakan dalam 1 pertemuan dengan mengukur sebelum pelatihan (pretest) dan setelah pelatihan berakhir (posttest). Data dianalisis dengan uji peringkat Wilcoxon menggunakan SPSS 25.0 untuk windows. Hasil penelitian menunjukkan bahwa: (1) terjadi peningkatan rasa syukur yang signifikan setelah diberikan terapi dzikir dengan hasil statistik (Z) = -2,677 dan p= 0,007 (p less than 0,05); (2) tidak terdapat perbedaan skor syukur sebelum dan sesudah pada kelompok kontrol yang tidak diberikan terapi dzikir dengan hasil statistik (Z) = -1,409 dan p= 0,159 (p more than 0,05).